Systems Dynamics and Serious Video Games in an Appropriation Strategy of a Decision Support System for Small Livestock Farmers - Gómez Prada, Urbano Eliécer; Orellana Hernández, Martha Lucía; Salinas Ibañez, Jesús María (International Journal of Interactive Mobile Technologies (iJIM), 2020)
This document presents a Decision Support System (DSS) aimed at small livestock farmers who have not made use of Information Technologies (IT) in their production systems. The DSS was built based on the finite difference equations of a simulation model in System Dynamics in whose definition the beneficiaries participated and also served as a base for the development of a serious video game. The DSS and the Serious video game is supported in a Web and Mobile Architecture. The simulation model and the serious video game are used as support tools in the training given to users to learn how to use the DSS. These three tools are the result of a doctoral research project, which used two methodologies during its execution: Design and Development Research and the Case Studies methodology. The tools were applied in an appropriation strategy with livestock farmers of the department of Santander in Colombia, where resistance to change and cultural attachment causes a low adoption of technology. The inclusion of gamification elements helps the user to understand the connection of these elements and their processes in a real farm, know the large volume of data managed by the DSS, enhance the process by making it more fun, improve the learning curve and provide useful data for tracking the use of the DSS. 16 months after the end of the training, the DSS has more than 13000 reported records about the activities of the farmers in their farms.